THE RELATIONSHIP OF SOCIAL SUPPORT WITH ACADEMIC BURNOUT EVENTS IN FINAL-LEVEL STUDENTS - Nurmansyah, Andri; Yani, Fifi Siti Fauziah; Jamiyanti, Anggi (REAL in Nursing Journal, 2024)
Background: Final year students are having a tough time, because there are many assignments and obligations to complete a thesis. At this time social support is really needed, usually students spend more time with their peers because social support from peers makes someone feel like they have friends to share the same interests with. Students who lack peer social support are at risk of experiencing academic burnout. This research aims to determine the relationship between peer social support and academic burnout in final year students at Bandung regional universities. Method: This research uses quantitative methods with correlational techniques. Subjects totaling 90 students were taken using the Simple Random Sampling. Data collection methods used the Maslach Burnout Inventory-Student Survey (MBI-SS) questionnaire, and peer social support questionnaires. Results: The research results showed that 68.9% of students had a low level of social support and 54.4% of students had a high level of academic burnout. The correlation test using Spearman Rank obtained a sig value of 0.017 <0.05. Conclusion there is a relationship between peer social support and the incidence of academic burnout in final year students at Bandung regional universities. It is hoped that future researchers can analyze other factors that can cause academic burnout.